Emerging electrochemical portable methodologies on carbon-based electrocatalyst for the determination of pharmaceutical and pest control pollutants: State of the art. Issue 1 (February 2023) - Mishra, Smriti; Singh, Sheelendra Pratap; Kumar, Pradip; Khan, Mohd. Akram; Singh, Shiv
Abstract: Disproportionate use of antibiotics and pesticides is a bone-chilling concern for the environment and humans as well. So, it is essential to monitor the contamination caused by antibiotics and pesticides using different efficient detection techniques. In this regard, electrochemical sensors have proved to be a powerful tool for detecting pesticides and antibiotics due to their various advantages including synergistic aspects, systematized fabrication procedures, easier detection, remarkable sensitivity and selectivity. This review discusses the fabrication of different electrochemical sensors for detecting antibiotics and pesticides in different analytes (food and water samples) using different carbon-based electrodes such as carbon nanotubes, graphene, and its oxide, nanomaterials with molecularly imprinted polymers, and various miscellaneous carbon materials – carbon dots, carbon nanofiber, carbon nanodiamond, etc. Finally, the review includes a look at the future concepts in this research area to assist in improving the detection techniques for antibiotics and pesticides. Graphical Abstract: ga1 Highlights: Electrochemical sensors for detection of antibiotics and pesticides. Working electrodes of the sensor were fabricated using carbon-based materials. Challenges and future perspectives of electrochemical sensors are discussed.